A DIACHRONIC STUDY OF THE AUTHORIAL IDENTITY IN TOURISM RESEARCH ARTICLES - Gusti Ayu Praminatih (Universitas Airlangga, 2020)
The use of first-person pronouns (I, we) in writing research articles was remaining problematic for both inexperienced and advanced authors. Nevertheless, some research suggested that the FPPs were increasingly used in writing research articles (RAs) to indicate the authorial identity. This research aimed to investigate types, functions, and correlation of the FPPs in tourism RAs by employing the diachronic corpus linguistics method. The data of this research were accessed and downloaded through five open access journals published by Elsevier. There were 80 selected tourism RAs from the year 2015 to 2020 that classified into five corpora. AntConc was software that was employed to retrieve the FPPs from the corpora. This research discovered the FPPs I and we were constructed as six types of authorial identity that range from the least to the strongest authoritative identity in the past five years. The constructed authorial identity had three main functions for the authors of tourism RAs, tourism as an academic discipline, and the readers of tourism RAs. The statistical calculation showed that the correlation was 0.87 that signified the use of the FPPs was increasing in the following year. Keywords: authorial identity, diachronic corpus linguistics, the first-person pronouns, tourism research articles.